Perbandingan Sistem Skoring Guy’s Stone Score dan S.T.O.N.E. Nephrolithometry Score dalam Memrediksi Stone Free Rate - Lumangkun, Ridel M.; Arianto, Eko; Kambey, Stefan A. G. P. (e-CliniC, 2024)
Abstract: Percutaneous nephrolithotomy (PCNL) is the primary surgical management for kidney stones larger than >20mm. The success of this procedure is assessed by monitoring the stone free rate (SFR). Currently, SFR can be predicted through validated scoring systems such as Guy’s stone score and S.T.O.N.E. nephrolithometry score. This study aimed to compare Guy’s stone score and S.T.O.N.E. nephrolithometry score in predicting SFR after PCNL at Prof. Dr. R. D. Kandou Hospital Manado. This was an observational and analytical study with a cross-sectional design. Data collection was conducted through patients’ medical record data. Data analysis was performed using the Fisher’s Exact Test and the independent t-test through SPSS Statistic Version 26 for MacOS. The results showed that there was no statistically significant relationship between Guy’s Stone Score and SFR after PCNL (p=0.706). The S.T.O.N.E. nephrolithometry score also showed no significant relationship with SFR after PCNL (p=0.514). In conclusion, both Guy’s stone score and S.T.O.N.E. nephrolithometry score do not have significant impact on predicting stone free rate in patients with kidney stone at Prof. Dr. R. D. Kandou Hospital Manado. Keywords: Guy’s stone score; S.T.O.N.E. nephrolithometry score; stone free rate    Abstrak: Percutaneous nephrolitotomy (PCNL) merupakan tatalaksana pembedahan utama batu ginjal berukuran >20mm. Tindakan ini dievaluasi dengan pemantauan stone free rate (SFR). Pada praktik klinis saat ini SFR dapat diprediksi melalui beberapa sistem skoring yang telah divalidasi seperti Guy’s stone score dan S.T.O.N.E. nephrolithometry score. Penelitian ini bertujuan untuk membandingkan kedua sistem skoring tersebut dalam memrediksi SFR setelah tindakan PCNL di RSUP Prof. Dr. R. D. Kandou Manado. Penelitian ini merupakan studi analitik observasional dengan desain potong lintang melalui evaluasi data rekam medik pasien. Uji statistik dilakukan dengan uji Fisher’s Exact Test dan independent t-test menggunakan program SPSS Statistic Version 26 for MacOS. Hasil penelitian menunjukkan tidak terdapat hubungan bermakna antara sistem skoring Guy’s stone score dengan SFR setelah tindakan PCNL (p=0,706). Sistem skoring S.T.O.N.E. nephrolithometry score juga tidak menunjukan hubungan bermakna dengan SFR setelah tindakan PCNL (p=0,514). Simpulan penelitian ini ialah sistem skoring Guy’s Stone Score dan S.T.O.N.E. nephrolithometry score tidak memberikan pengaruh bermakna dalam memrediksi stone free rate pada pasien batu ginjal di RSUP Prof. Dr. R. D. Kandou Manado Kata kunci: Guy’s stone score; S.T.O.N.E. nephrolithometry score; stone free rate